BAMBOO FRAME DUCT SOLAR DRYER - Akash A. Pawar; Shivraj Mahesh Pawar; Akash Hanumant Sawase; Yash Santosh Korade; Devdatta Vijay Chavan (International Journal of Innovations in Engineering Research and Technology, 2022)
Drying is one of the methods used to preserve food products for longer periods. The heat from the sun coupled with the wind has been used to dry food for preservation for several years. In many countries of the world, the use of solar thermal systems in the agricultural area to conserve vegetables, fruits, coffee and other crops has shown to be practical, economical and the responsible approach environmentally. Solar heating systems to dry food and other crops can improve the quality of the product, while reducing wasted produce. Under the module of Advance topics in mechanical engineering projects, we were assigned to design the low-cost vegetable dryer. The design of dryer consists of several steps and sequence procedure. Drying or dehydration of a material say by employing solar energy means removal of moisture from the interior of the material to the surface and then to remove this moisture from the surface of the drying material. It is a complex heat and mass transfer process.